Hydrogen peroxide electrosynthesis via regulating the oxygen reduction reaction pathway on Pt noble metal with ion poisoning. (1st March 2021) - He, Dequan; Zhong, Lijie; Gan, Shiyu; Xie, Jingxin; Wang, Wei; Liu, Zhenbang; Guo, Wen; Yang, Xin; Niu, Li
Highlights: A concept of isolating active sites by ion poisoning for the electrosynthesis of H2 O2 . SCN − was screened as the most efficiently poisoned Pt/C catalysts for two-electron ORR. The catalysts exhibited high activity and selectivity towards H2 O2 production in acidic media. Abstract: Precious metal-based catalysts have been explored intensively for the electrocatalysis of oxygen reduction reaction (ORR). Alloying with heteroatoms, for instance, Hg to isolate precious metal sites are reported to convert the ORR from four-electron (4e − ) to two-electron (2e − ) pathway. The 2e − ORR could be used for the electrochemical production of hydrogen peroxide (H2 O2 ) as a sustainable route instead of industrial anthraquinone-mediated catalysis. Isolating active sites provides a breakthrough strategy to regulate electron transfer pathway of ORR. However, the highly toxic mercury limits the practical use. Herein we employ a simple ion poisoning strategy, by virtue of the strong ion coordination effects to regulate the classic Pt/C catalyst for the electrochemical H2 O2 production through ORR in acid media. The representative SCN − poisoned Pt/C catalyst displayed high activity and selectivity of over 90% at a wide range of potentials. The stability tests showed negligible performance lost after 30 hours. The present work offers a promising poisoning strategy to regulate precious catalysts for selectively electrochemical production of H2 O2 . Graphical abstract: Image, graphical abstract